Analysis of gaming actions of the central blocking in competitive activity of women's volleyball amateur teams - Strelnykova, I.; Mel`nik, A.; Liakhova, T. (Slobozhanskyi herald of science and sport, 2018)
Purpose: determine the quantitative indicators of the game actions of the central blocking amateur teams in competitions under the aegis Volleyball Federation of Kharkiv region.